Social mobility of ethnic minority students in Laos - Faming, Manynooch (The Australian journal of anthropology, 2019)
Idealistically speaking, schools are engines for upward social mobility. Education for ethnic minorities in Laos was set up to achieve nationalist, political, economic and sociocultural goals of ‘equity’ and ‘equality’. It was hoped that education would shift ethnic minorities from a lifestyle based on superstitious beliefs to a modern one, so that they could participate and enjoy ‘equality’ through educational equity. The purpose of this paper is to provide a case study of how equality as a promise in education has impacted on students’ upward mobility, particularly the political discourse of the ‘big man’. This paper explores social mobility provided by national education for ethnic minorities through boarding schooling. It finds that such education has yet to reposition ethnic minorities into the ethnic Lao sociocultural hierarchy. As a result, regardless of their educational success, students are still ranked as ‘ethnic minorities’ and as being ‘poor’ in the eyes of urban students, middle class and rich students, and the ethnic Lao elite.